2005
DOI: 10.1103/physrevb.72.035438
|View full text |Cite
|
Sign up to set email alerts
|

Size calibration of self-assembled nanoparticles in a model of strained epitaxy with passive substrate

Abstract: We argue that a transient size calibration of self-assembled nanoparticles during strained epitaxy can be caused by forces interior to the growing islands without substrate-propagated interparticle interactions or intermixing with the substrate. The role of substrate in our mechanism is only to provide the intraparticle elastic strain. Our arguments are based on kinetic Monte Carlo simulations of the ͑1+1͒-dimensional model of strained epitaxy of Ratsch and Zangwill ͑RZ͒ ͓Surf. Sci. 293, 123 ͑1993͔͒. It has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…As is seen, the reduced energy in the square dot is equal to twice the energy in a linear 1D chain of stacks of atoms of height h [28,38,18]. This is because each atom in the island belongs to two orthogonal chains, the interactions within which are independent due to the approximations used.…”
Section: The Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…As is seen, the reduced energy in the square dot is equal to twice the energy in a linear 1D chain of stacks of atoms of height h [28,38,18]. This is because each atom in the island belongs to two orthogonal chains, the interactions within which are independent due to the approximations used.…”
Section: The Modelmentioning
confidence: 96%
“…Therefore, atomistic models have been developed with the aim of addressing this important problem with the use of the exact kinetic Monte Carlo (KMC) simulations [14][15][16][17][18][19][20][21][22]. The main difficulty hampering the microscopic simulations is posed by the long-range forces due to the epitaxial strain caused by the lattice size mismatch between the substrate and the overlayer.…”
Section: Introductionmentioning
confidence: 99%
“…Since the lattice mismatch between the two materials is very large, the FM mode confirms that there are likely few, if any, covalent bonds between the Ge layer and the underlying graphene, confirming the VdW bonding nature of our system. [18][19] The weak bond strength, typical of VdW, favors the elastic relaxation of the Ge germs. It is worth to note that the 2D nature of the germs is corroborated by the fact that we did not notice any multilayer germs or layer stacking (except for the case where the second layer is on the opposite surface of the SLG).…”
Section: Nucleation Of Ge On S-slgmentioning
confidence: 99%
“…Some attribute it to straininduced equilibrium states while others propose that the island edge effect induces a stable island size against ripening [4,5]. Besides the factors external to growing islands, it has also been shown that the size selection of islands could be achieved via the forces confined to the interiors of the islands [6]. For metals, the size distribution of 3D metal islands is broad in general [7][8][9][10] in spite of some reports on uniform 3D metal islands such as Au on TiO 2 surface and Fe on the NaCl(0 0 1) surface [11,12].…”
Section: Introductionmentioning
confidence: 99%